A phase II trial of lenalidomide plus rituximab in previously untreated follicular non-Hodgkin’s lymphoma (NHL): CALGB 50803 (Alliance) - Martin, P (Ann Oncol, 2017)
BACKGROUND: This multicenter, phase II trial tested the tolerability and efficacy of lenalidomide plus rituximab in patients with previously untreated follicular lymphoma (FL). PATIENTS AND METHODS: Patients with grade 1–3a FL, stage 3–4 or bulky stage 2, FL international prognostic index (FLIPI) 0–2, and no prior therapy were eligible to receive rituximab 375 mg/m(2) weekly during cycle 1 and day 1 of cycles 4, 6, 8, and 10, plus lenalidomide 20–25 mg on days 1–21 for twelve 28-day cycles. The primary objectives were to evaluate response rates [complete (CR) and overall] and time to progression. Secondary objectives included toxicity, response according to polymorphisms in FcgR2A and FcgR3A, and changes in circulating pro-angiogenic cells. RESULTS: From October 2010 to September 2011, 66 patients were enrolled. Median age was 53 years, 34 were female, 15 had bulky disease, 21 were FLIPI 0-1, 43 FLIPI 2, and 2 FLIPI 3. One patient withdrew before receiving treatment. Fifty-one patients completed 12 cycles of lenalidomide. Reasons for discontinuation included withdrawal (n = 6), adverse events (n = 6), progression (n = 2). Grade 3–4 hematologic toxicity included neutropenia (21%), lymphopenia (9%), and thrombocytopenia (2%), infection (11%), and rash (8%). Grade 1–2 toxicity included fatigue (78%), diarrhea (37%), rash (32%), and febrile neutropenia in one patient. The overall response rate was 95%; the CR rate was 72% (95% confidence interval, 60% to 83%). With a median follow-up of 5 years, the 2- and 5-year progression-free survival were 86% and 70%, respectively, and the 5-year overall survival was 100%. There was no association between CR rate or PFS and FLIPI, histological grade, bulky disease, FcgR2A/FcgR3A polymorphism, or change in circulating endothelial cell/hematopoietic progenitor cell. CONCLUSION: Lenalidomide plus rituximab was associated with low rates of grade 3–4 toxicity, yielded a CR rate and PFS similar to chemotherapy-based treatment and may represent a reasonable alternative to immunochemotherapy in previously untreated FL. CLINICALTRIALS.GOV IDENTIFIER: NCT01145495.